HPV vaccine uptake among adolescent girls in Nigeria: The complex role of caregivers' education. - Sohail Agha; Ifeanyi Nsofor (PLoS ONE, 2025)
Introduction Cervical cancer remains a leading cause of cancer-related deaths among women in low- and middle-income countries (LMICs), with sub-Saharan Africa (SSA) bearing a disproportionate burden of the disease. Human papillomavirus (HPV) vaccination offers a critical intervention, yet uptake remains suboptimal due to vaccine hesitancy, misinformation, and socio-economic disparities. This study examines factors associated with HPV vaccine uptake among adolescent girls whose caregivers use social media. Methods We conducted a cross-sectional survey in October and November 2024 among 4,830 caregivers of adolescent girls 9-17 in Abuja, Nasarawa, and Adamawa states. Participants were recruited via advertisements on Facebook and Instagram. Data on adolescents' HPV vaccination was collected from caregivers. Caregiver also provided data on their own education, motivation, ability, and exposure to HPV vaccine messaging. Multivariate logistic regression was used to identify predictors of vaccine uptake, adjusting for socio-demographic factors, motivation, and ability. Results The HPV vaccination rate among adolescent girls 9-17 was 53.9%. Caregivers with no formal education had higher exposure to HPV campaign messaging than caregivers with Higher National Diploma (HND) or Bachelor's (BSc) education (95.3% vs 53.8%, p < 0.001). The least educated caregivers were also more likely to report a three times higher odds ratio of HPV vaccination compared to caregivers with Higher National Diploma (adjusted odds ratio [aOR] = 3.01, 95% CI: 1.52-5.93). Exposure to HPV vaccine messaging was associated with a seven times higher odds ratio of HPV vaccine uptake (aOR = 6.87, 95% CI: 6.20-7.61). Motivation and ability were positively associated with HPV vaccination. Regional differences were observed, with Nasarawa demonstrating higher a vaccination rate than Abuja and Adamawa. Conclusion Exposure to HPV vaccine messages is higher among less educated compared to more educated caregivers. Moreover, the impact of advertising exposure on vaccine uptake is stronger among less educated caregivers. Educational disparities in campaign exposure and campaign effects highlight the need for strategies to increase campaign reach to more educated caregivers and to ensure that HPV messages resonate with them. Our findings suggest that existing campaigns may need to be restructured to more effectively reach educated and skeptical audiences.